Stratigraphic model of a Middle-Late Jurassic carbonate system (Mozduran Ridge, Kopet Dagh area, NE Iran). (June 2021) - Noemani Rad, Rooholah; Do Couto, Damien; Brunet, Marie-Françoise; Pomar, Luis; Fürsich, Franz T.; Moallemi, Seyed Ali; Gorini, Christian
Abstract: Lithostratigraphy and biostratigraphy of Middle to Upper Jurassic carbonate platforms of the Eastern Kopet Dagh (EKD), northeastern Iran were assessed. Up to 3000 m of sedimentological logs located along ten stratigraphic sections were investigated. At least five types of carbonate production systems were identified in the study area: (1) a mud-dominated platform carbonate topped by (2) an off-platform carbonate grain-production system, (3) a grain-reworking system deposited within basinal settings (gravity-driven reworking), (4) mounds built by tubular sponges and corals, and (5) prograding oolitic wedges. The first carbonate production system (Callovian‒early Oxfordian) yields platy and solitary corals, together with stromatactis-like structures. The second carbonate production system is represented by upper Oxfordian off-platform grainstones. These two carbonate production systems comprise the Khaneh Zou Fm. The third system is characterised by oncoids, originating from the carbonate platforms. These oncoids, together with bioclasts, were transported into the Kimmeridgian hemipelagic succession of the Chaman Bid Fm. The last two carbonate production systems are common in the Mozduran Fm. Tithonian tubular sponges-corals mounds, and their related dismantling products constitute a major characteristic system of the Mozduran Fm. Shallowing-upward prograding clinoforms are a second characteristic system of the Mozduran Fm., whereby ooids, generated under shallow-water conditions, were shed downslope to form interbeds within basinal mudstones. Our findings suggest that the combination of 2nd order eustatic sea-level changes with hydrodynamic processes as well as rift-inherited morphologies and climatic changes controlled the development and lateral facies evolution of the Middle to Upper Jurassic carbonate platforms. The description of these carbonate systems and of their morphology, together with stratigraphic interpretations may lead to exploration of complex structural-stratigraphic traps, thereby highlighting new potential hydrocarbon reservoirs in the EKD. Highlights: Three possible carbonate platforms were developed during Callovian-Tithonian in the Eastern Kopet Dagh. At least five types of carbonate production systems were identified. New regional stratigraphical and depositional models with detailed biostratigraphic data are presented.